EFEKTIFITAS METODE PICTURE AND PICTURE UNTUK MENINGKATKAN HASIL BELAJAR KIMIA MATERI KONFIGURASI ELEKTRON DAN DIAGRAM ORBITAL PADA SISWA KELAS X IPA 6 MAN 2 PALU - Eniwati (Koordinat Jurnal MIPA, 2023)
The purpose of this study was to determine the increase in learning outcomes of chemistry learning materials electron configurations and orbital diagrams in class X IPA 6 MAN 2 Palu City using the picture and picture method. The type of research used is classroom action research using test techniques as a data collection method. Data analysis used descriptive analysis. The results of the study revealed that the application of the picture and picture method in chemistry lessons on configuration materials and orbital diagrams could improve the learning achievement of students in class X IPA 6 MAN 2 Palu City. The learning outcomes are evidenced by the increase in the average value of student learning outcomes in each cycle. In the pre-cycle, the average learning score of students was 58.33 from a total of 36 students with 13 students who completed. In the first cycle, the number of students completed was 21 out of a total of 36 students or 68.89. This increase continued in the second cycle with the number of students reaching 30 students out of a total of 36 or 80.83. Also occurred in the percentage of minimum completeness criteria increased from 36.11% in the pre-cycle to 58.33% in the first cycle and increased to 83.33% in the second cycle.